The Effects of Universal Public Childcare Provision on Cases of Child Neglect and Abuse - Malte Sandner; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2018)
We investigate the impact of childcare provision on cases of child abuse and neglect in Germany between 2002 and 2014. For identification, we exploit a governmental reform introducing mandatory early child care. The implementation at the county level generated large temporal and spatial variation in childcare coverage. Our measure of child abuse and neglect comes from a unique high-quality administrative data set that covers all child protection cases at the German county level. The estimated ITT effect shows a decline by 0.24 cases per 1,000 children if a county increases childcare slots above the median, which is a reduction of 21.4 percent from the mean. This finding is of high economic relevance given the enormous costs of child abuse and neglect for the society. Our results show that the provision of universal public child care can be an effective policy to prevent part of these costs.
Keywords: J13; J12; I38; 330; child abuse and neglect; early child care; prevention